The opinion of divers on the interpretation of marine geology in the archipelago of Fernando de Noronha (Brazil) - Tatiane Ferrari do Vale; Rafael Altoe Albani; Jasmine Cardozo Moreira (Journal of the Geological Survey of Brazil, 2021)
Environmental interpretation seeks to reveal meanings to provoke personal connections between the public and the protected heritage. In the specific case of geological heritage, it determines and communicates the meaning of a geological and geomorphological phenomenon, event or location. There is a range of nature tourism activities that can promote interpretation of this heritage. The practice of properly organized scuba diving can bring benefits both for conservation of the environment and for local communities. Fernando de Noronha is one of the best dive sites in the world and actions focused on aspects of marine geology add even more value to the activity. In this sense, we sought to investigate by applying a questionnaire on the opinion of divers on environmental interpretation and aspects of marine geology in the archipelago. The questionnaire was applied online between April 2018 and May 2019, with 100 individuals who practiced scuba diving in the archipelago at least once. Different data collection techniques were applied for data collection (convenience, quota and snowball). The main results indicate that information on marine geology is relevant for the carrying out scuba diving, and actions in this sense are able to contribute to a more conscious posture regarding island sustainability.